Role Of Ushapana In Influencing Rejuvenation And Lifespan - Rajpurohit, Abhisek; Mishra, Pramod Kumar; Parashar, Rahul; Sharma, Aakanksha; Sharma, Indumati (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda’s holistic approach focuses on illness prevention, promotion, preservation, and cure. Everyone wants to appear young constantly and to live a longer life by staying healthy. Ageing is a complex and unavoidable process that begins before birth and should last for the rest of its life. Ayurveda, one of the world’s most authoritative mind-body-spirit medicinal systems, offers various concept of the aging process. This system of medicine includes therapies for healthy aging so as to create an optimal health and lengthen an individual’s health span by living in harmony with nature. The daily routine of ushapana (dawn water) is a fairly widespread ayurvedic practice in India. After waking up, drink a glass of lukewarm or room temperature water. A person who drinks water from eight prasriti (a cup created by uniting two palms) before sunrise can live for a hundred years without disease or fear of old age. Ushapana is one of the Ayurvedic Dincharya (day regiman) procedures which play a very important role in influencing rejuvenation and lifespan.